How Background Influences School Counselors' Career Calling: A Preliminary Study - Alfan, Robbani; Solehuddin, M; Nurihsan, Juntika; Riksa Yustiana, Yusi (Bulletin of Counseling and Psychotherapy, 2024)
This study explores the variations in career calling among school counselors based on ethno-socio-demographic backgrounds, such as ethnicity, religion, employment status, age, and gender. Utilizing a comparative research design, this study involving 95 school counselors analyzes how these factors influence the level of career calling among counselors. The findings indicate that while there are differences in career calling between groups, these differences are not statistically significant. These results highlight that career calling develops through a complex interaction of intrinsic and extrinsic factors and is not entirely dependent on formal variables such as education or employment. This research makes a significant contribution to the literature on career calling, particularly within the context of school counselor professionalism in Indonesia, and offers valuable insights for the development of more inclusive policies and intervention programs.